Prevalence and Outcomes of Coagulase-Negative Staphylococci in Newborns Admitted to the NICU in a Tertiary Hospital in Libya (Razi Medical Journal, 2025)
Neonatal sepsis caused by coagulase-negative Staphylococcus (CoNS) poses significant challenges in NICUs, particularly in preterm infants, with diagnostic uncertainty and antimicrobial resistance complicating care. This retrospective study of 411 neonates admitted to the NICU at Zawia Medical Center in the year 2012. The prevalence of CoNS was 10.5%. Cesarean section (C/S) was a key risk factor, with 79.1% of CoNS-positive neonates delivered via C/S versus 52.9% in CoNS-negative cases (p =0.001), suggesting disrupted maternal microbiome transmission and nosocomial exposure. While prematurity (55.8% vs. 51.4%) and low birth weight (60.5% vs. 50.8%) were more prevalent in CoNS-positive infants, these associations lacked significance. Notably, CRP positivity surged post-deterioration in CoNS cases (93% vs. 21.5%; p
Keywords: Neonatal Sepsis, Coagulase-Negative Staphylococcus, Cesarean Section, C-Reactive Protein, Nosocomial Infections.